Identification of plant growth promoting rhizobacteria around Pulang Pisang Food Estate, Central Kalimantan, Indonesia - Lutfi Tri Andriani; Susilo Hambeg Poromarto; Supyani Supyani; Edi Purwanto; Hadiwiyono Hadiwiyono (Universitas Lampung, 2025)
Plant growth-promoting bacteria are well known as biostimulants, biofertilizers, bioprotectants, and biodegraders. The Pulang Pisau Food Estate is an Indonesian government program aimed at increasing rice crop production to achieve sustainable food self-sufficiency. Research on rhizobacteria in the Pulang Pisau Food Estate area is still relatively limited. In this study, we conducted in vitro assays to evaluate the potential of indigenous bacterial isolates from the Pulang Pisau Food Estate as plant growth-promoting rhizobacteria (PGPR). The study focused on four bacterial isolates, which were tested for plant growth-promoting traits including phosphate solubilization, indole-3-acetic acid (IAA) production, effects on rice seed germination, and detached leaf assays to assess the ability of rhizobacteria to inhibit bacterial pathogens. The results of 16S rRNA gene identification suggested that isolates UNS-P1, UNS-P3, and UNS-R1 were closely related to Bacillus cereus, while one previously identified isolate (UNS-R2) was confirmed as Bacillus subtilis. All bacterial strains were able to produce IAA, while only one isolate demonstrated the ability to solubilize phosphate. In the germination test, no significant differences were observed in root length, but a significant difference in shoot (plant) height was detected. Bacillus subtilis (UNS-R2), at a 10³ dilution, resulted in significantly greater plant height compared to other treatments. Among the four bacterial isolates, only one showed the ability to inhibit the pathogen Pantoea ananatis. These results suggest that indigenous bacterial isolates from the Pulang Pisau Food Estate have potential as plant growth-promoting rhizobacteria (PGPR) and may contribute to enhancing plant growth and serve as biocontrol agents against P. ananatis.